Peran Vlog dalam Perkembangan Pola Pikir Siswa Sekolah Menengah Kejuruan Teknologi Informasi Komputer Darussalam Medan - Muya Syaroh Iwanda Lubis; Asrindah Nasution; Muhammad Luthfi (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2020)
This article or article aims to develop students' talent into the world of Vlogs, not to be careless and have a negative impact, and to train the mindsets of adolescents to continue to develop according to the changes and developments of the times without ignoring the moral role in them. To approach this problem the theoretical reference from the Communication Technology book by Nurudin was used. Data collected through interviews, observation and documentation. Qualitative data analysis techniques using: Reduction, presentation and conclusion drawing. This study concludes that the role of Vlogs is in great demand by students in Indonesia, especially SMK TIK Darussalam. So that the development of their mindset develops when they have to think of what Vlog videos are good for public publication. By seeing Vlogs produced by others, students are able to hone the development of their thought patterns so that they can understand Vlog videos that are positive or negative for publication. That way what they do has a positive value for themselves, the school and the community